Solar cell module and method for manufacturing the solar cell module
Patent Information
- Application Number
- JP2024012048
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-01-30
Smart Images

Figure 0007631573000001_ABST
Abstract
Description
[Technical field]
[0001] SUMMARY OF THE DISCLOSURE Embodiments of the present invention relate to a solar cell module and a method for manufacturing a solar cell module. [Background technology]
[0002] Known photoelectric conversion elements include those having a photoactive layer made of a material with a perovskite crystal structure (hereinafter referred to as a perovskite layer) as the photoactive layer.
[0003] In a multi-layer junction photoelectric conversion element having a perovskite layer, the perovskite layer is exposed at the end surface due to its structure. Therefore, the perovskite layer is damaged by moisture generated from the sealing material during sealing and in a vacuum and overheated state. Therefore, vacuum lamination is generally performed at a low temperature and for a short time so as not to damage the perovskite layer. However, if the lamination conditions deviate from those recommended for the sealing material, the crosslinking rate and gelation rate may be insufficient, and the sealing material may not be able to exhibit its original performance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2016 / 158838 Summary of the Invention [Problem to be solved by the invention]
[0005] The problem to be solved by the present invention is to provide a solar cell module in which the perovskite layer is protected from outside air and moisture and durability is improved, and a method for manufacturing the solar cell module. [Means for solving the problem]
[0006] The solar cell module of the embodiment includes a laminate, a protective layer, and a sealing material. The laminate is formed by laminating a first electrode, a first photoactive layer, an intermediate conductive layer, a second photoactive layer made of a photoactive material having a perovskite crystal structure, and a second electrode. A protective layer covers at least an edge surface of the second photoactive layer. The sealing material seals the laminate via the protective layer. The water vapor transmission coefficient of the protective layer is less than the water vapor transmission coefficient of the encapsulant. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a cross-sectional view showing a solar cell module according to a first embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing a solar cell module according to a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, a solar cell module and a method for manufacturing a solar cell module according to an embodiment will be described with reference to the drawings.
[0009] [Solar cell module] (First embodiment) FIG. 1 shows a solar cell module 1 of the first embodiment. The solar cell module 1 shown in FIG. 1 is composed of a laminate 7 in which a first electrode 2, a first photoactive layer 3, an intermediate conductive layer 4, a second photoactive layer 5 made of a photoactive material having a perovskite crystal structure, and a second electrode 6 are laminated, a protective layer 8 that covers the laminate 7, and a sealant 9 that seals the laminate 7 via the protective layer 8. The second electrode 6 is composed of a transparent electrode layer 10 and a metal electrode layer 11. A first substrate 12 is provided on a surface 9a of the sealant 9 on the first electrode 2 side. A second substrate 13 is provided on a surface 9b of the sealant 9 on the second electrode 6 side. A first extraction electrode 14 is connected to the first electrode 2. A second extraction electrode 15 is connected to the metal electrode layer 11 of the second electrode 6. In the solar cell module 1 shown in FIG. 1, light is taken in from the second electrode 6 side, and electricity is generated in the first photoactive layer 3 and the second photoactive layer 5, respectively. The generated current is then taken out from the first extraction electrode 14 and the second extraction electrode 15.
[0010] On an end face 7a of the laminate 7, an end face 3a of the first photoactive layer 3, an end face 4a of the intermediate conductive layer 4, an end face 5a of the second photoactive layer 5, and an end face 10a of the transparent electrode layer 10 are located.
[0011] In the solar cell module 1 shown in FIG. 1, a first buffer layer 16 may be provided between the second photoactive layer 5 and the protective layer 8, specifically, between the intermediate conductive layer 4 and the second photoactive layer 5.
[0012] In the solar cell module 1 shown in FIG. 1, a second buffer layer 17 may be provided between the second photoactive layer 5 and the protective layer 8, specifically, between the second electrode 6 and the second photoactive layer 5.
[0013] In the solar cell module 1 shown in FIG. 1, an anti-reflection layer 18 may be provided between the second photoactive layer 5 and the protective layer 8, specifically, between the metal electrode layer 11 and the transparent electrode layer 10.
[0014] At the end face 7a of the laminate 7, an end face 16a of the first buffer layer 16, an end face 17a of the second buffer layer 17, and an end face 18a of the antireflection layer 18 are located.
[0015] The first electrode 2 can be made of any conventionally known material as long as it is conductive. The material of the first electrode 2 may be gold, silver, copper, platinum, aluminum, titanium, iron, palladium, or the like, with aluminum or silver being preferred.
[0016] The first photoactive layer 3 is composed of a crystalline silicon layer of a first conductivity type. The crystalline silicon constituting the first photoactive layer 3 can adopt a structure similar to that of silicon generally used in photovoltaic cells. Specifically, crystalline silicon containing crystalline silicon such as single crystal silicon, polycrystalline silicon, and heterojunction silicon can be mentioned. The crystalline silicon may also be a thin film cut out from a silicon wafer. As the silicon wafer, n-type silicon crystal doped with phosphorus, arsenic, etc., and p-type silicon crystal doped with boron, gallium, etc. can also be used. Since electrons in p-type silicon crystal have a long diffusion length, p-type crystalline silicon is preferable as the crystalline silicon of the first conductivity type.
[0017] The thickness of the first photoactive layer 3 is preferably from 50 μm to 500 μm, and more preferably from 100 to 300 μm.
[0018] The intermediate conductive layer 4 is disposed so as to be in contact with the first photoactive layer 3. The intermediate conductive layer 4 electrically connects the bottom cell mainly made of the first photoactive layer 3 and the top cell mainly made of the second photoactive layer 5 while isolating them, and has the function of guiding light not absorbed by the second photoactive layer 5 to the first photoactive layer 3.
[0019] The material of the intermediate conductive layer 4 can be selected from transparent or semi-transparent conductive materials. Such materials include conductive metal oxide films. Specifically, indium oxide, zinc oxide, tin oxide, and their composites such as indium tin oxide (ITO) and indium zinc oxide (IZO) are used. The transparent conductive layer 204b made of such metal oxides can be formed by a generally known method. Specifically, it can be formed by sputtering.
[0020] The total thickness of the intermediate conductive layer 4 is preferably 5 nm to 70 nm. If it is thinner than 5 nm, there will be many film defects, resulting in insufficient isolation of the layers adjacent to the intermediate conductive layer 4. If it is thicker than 70 nm, the light transmittance will decrease due to the diffraction effect, which may lead to a decrease in the amount of power generation on the first photoactive layer 3 side.
[0021] The second photoactive layer 5 is made of a photoactive material having a perovskite crystal structure. The perovskite crystal structure refers to the same crystal structure as perovskite. Typically, the perovskite structure is composed of ions A, B, and X, and the perovskite structure may be formed when ion B is smaller than ion A. The chemical composition of this crystal structure can be represented by the following general formula (1).
[0022] ABX3(1)
[0023] Here, A can be a primary ammonium ion. Specifically, CH3NH3 + (hereinafter referred to as MA), C2H5NH3 + , C3H7NH3 + , C4H9NH3 + , and HC(NH2)2 + (hereinafter referred to as FA), etc. + is preferable, but not limited to this. A is also preferably Cs + Also preferred are, but not limited to, 1,1,1-trifluoro-ethylammonium iodide (FEAI).
[0024] In addition, B is a divalent metal ion, Pb 2+ or Sn 2+ is preferable, but not limited to this. X is preferably a halogen ion, for example, F - , Cl - , Br - , I - , and At - is selected from Cl - , Br - , I - is preferred, but is not limited to this.
[0025] The materials constituting ions A, B, and X may be single or mixed. The constituent ions do not necessarily have to match the stoichiometric ratio of ABX3 to function.
[0026] The ions A constituting the perovskite of the second photoactive layer 5 are preferably composed of an atomic weight or the total atomic weight (molecular weight) of the ions constituting the ions of 45 or more. More preferably, it is preferable to include ions of 133 or less. Since the ions A under these conditions have low stability alone, they may be mixed with general MA (molecular weight 32). However, mixing MA approaches the band gap of silicon of 1.1 eV, which is not preferable as a tandem that divides wavelengths to improve efficiency, as the overall characteristics are reduced. In addition, when the ions A are a combination of multiple ions and include Cs, it is more preferable that the ratio of the number of Cs to the total number of ions A is 0.1 to 0.9.
[0027] This crystal structure has a unit lattice of a cubic, tetragonal, rectangular, etc., with A at each vertex, B at the body center, and X at the center of each face of the cubic crystal centered on A. In this crystal structure, an octahedron consisting of one B and six Xs contained in the unit lattice is easily distorted by interaction with A, and undergoes a phase transition to a symmetrical crystal. It is presumed that this phase transition dramatically changes the physical properties of the crystal, causing electrons or holes to be released outside the crystal, generating electricity.
[0028] Increasing the thickness of the second photoactive layer 5 increases the amount of light absorption and the short-circuit current density (Jsc), but the carrier transport distance increases, and the loss due to deactivation tends to increase. Therefore, there is an optimal thickness to obtain maximum efficiency. Specifically, the thickness of the second photoactive layer 5 is preferably 30 to 1000 nm, and more preferably 60 to 600 nm.
[0029] The transparent electrode layer 10 is a transparent or semi-transparent conductive layer. The transparent electrode layer 10 may have a structure in which a plurality of materials are laminated. In addition, since the transparent electrode transmits light, it can be formed on the entire surface of the laminate.
[0030] Examples of materials for the transparent electrode layer 10 include conductive metal oxide films and semitransparent metal thin films. Specifically, indium oxide, zinc oxide, tin oxide, and their composites such as indium tin oxide (ITO), indium zinc oxide (IZO), fluorine-doped tin oxide (FTO), and films made of conductive glass made of indium zinc oxide (NESA, etc.), aluminum, gold, platinum, silver, copper, etc. are used. In particular, metal oxides such as ITO or IZO are preferred. The transparent electrode layer 10 made of such metal oxides can be formed by a commonly known method. Specifically, it is formed by sputtering.
[0031] The transparent electrode layer 10 preferably has a thickness of 30 to 300 nm. If the transparent electrode layer 10 is thinner than 30 nm, the conductivity tends to decrease and the resistance tends to increase. High resistance may cause a decrease in photoelectric conversion efficiency. On the other hand, if the transparent electrode layer 10 is thicker than 300 nm, the flexibility of the electrode tends to decrease. As a result, if the thickness is large, the electrode may crack when stress is applied. The transparent electrode layer 10 may have a single layer structure or a multi-layer structure in which layers made of materials with different work functions are laminated.
[0032] The metal electrode layer 11 may be made of any conductive material, specifically, gold, silver, copper, platinum, aluminum, titanium, iron, palladium, or other conductive materials.
[0033] The metal electrode layer 11 has a shape in which a plurality of metal wires are arranged substantially in parallel. The thickness of the metal electrode layer 11 is preferably, for example, 30 to 300 nm. If the thickness of the metal electrode layer 11 is thinner than 30 nm, the conductivity tends to decrease and the resistance tends to increase. If the resistance increases, this may cause a decrease in photoelectric conversion efficiency. If the thickness of the metal electrode layer 11 is 100 nm or less, it is preferable because it has optical transparency and can improve power generation efficiency and light emission efficiency. The metal electrode layer 11 may have a single layer structure or a multi-layer structure in which layers made of different materials are laminated.
[0034] In the solar cell module 1 shown in FIG. 1, the water vapor permeability coefficient of the protective layer 8 is smaller than the water vapor permeability coefficient of the sealing material 9 .
[0035] The water vapor permeability coefficient of the protective layer 8 is 0.1 g mm / m, which is smaller than that of general sealing materials. 2 / day or less is preferable, and 0.08g mm / m 2 / day or less is more preferable, and 0.02g mm / m 2 / day or less is more preferable. If the water vapor permeability coefficient of the protective layer 8 exceeds the upper limit, the second photoactive layer 5 cannot be protected from the outside air and moisture.
[0036] The material of protective layer 8 is not particularly limited as long as the water vapor permeability falls within the above range, but a paraxylylene-based polymer or an amorphous fluoropolymer is preferred because of its low water vapor permeability, excellent light transparency, and excellent adhesion to second photoactive layer 5. The water vapor permeability of paraxylylene-based polymers is 0.08 g mm / m 2 / day, and the water vapor permeability coefficient of amorphous fluoropolymer is 0.02 g mm / m 2 / day. Furthermore, the water vapor transmission coefficient quantifies the transmission of the film material, but by using a material with high surface energy, it is possible to prevent the outflow of low molecular weight components such as water from the outside, and the outflow of the perovskite components from the inside. Surface energy can be measured by contact angle. The contact angle of EVA, a common sealing material, is 88.1°, while the contact angle of paraxylylene polymers is 114-149°, and the contact angle of amorphous fluoropolymers is 112-114°.
[0037] A paraxylylene-based polymer is represented by the following formula (1), where C is carbon and X is selected from hydrogen or halogen. One or more types of halogen are selected from chlorine, fluorine, etc. A portion of the hydrogen bonded to the carbon constituting the six-membered ring can be substituted with a halogen. One or more types of halogen are selected from chlorine, fluorine, etc. n means a repeating structure. The following formula (2) shows a more preferred structure of a paraxylylene-based polymer, in which X is hydrogen and a portion of the hydrogen bonded to the carbon constituting the six-membered ring is substituted with chlorine. n means a repeating structure.
[0038] [ka]
[0039] [ka]
[0040] The amorphous fluoropolymer is not particularly limited, but preferably has a structure shown in the following formula (3) in the main chain. X represents an end group and includes carbon, oxygen, hydrogen, nitrogen, and silicon elements, and is particularly preferably -CF3, -COOH, -CONH-C3H6-Si(OC2H5)3, -CONH-C2H4-N(C2H4-NH2)2, etc. n represents a repeating structure.
[0041] [ka]
[0042] The water vapor permeability coefficient of the material of protective layer 8 can be measured, for example, by introducing water vapor onto one side of a film-like sample, passing through the film, and calculating the amount of water vapor detected on the opposite side of the film.
[0043] The thickness of the protective layer 8 is preferably 0.01 μm or more and 10 μm or less, more preferably 0.05 μm or more and 4 μm or less, and even more preferably 0.4 μm or more and 0.9 μm or less. If the thickness of the protective layer 8 is less than the lower limit, not only the amount of gas permeation increases due to the reduction in the thickness of the protective layer 8, but also the occurrence of pinholes becomes significant, and a sufficient water vapor permeability coefficient cannot be obtained. Furthermore, the effect of preventing the intrusion of low molecular components such as moisture generated during vacuum lamination and subsequent power generation is reduced. Also, the effect of preventing the outflow of components constituting perovskite during vacuum lamination and subsequent power generation is reduced. As a result, the solar cell characteristics are reduced immediately after sealing, and the power generation time is shortened. If the thickness of the protective layer 8 exceeds the upper limit, the amount of gas permeation decreases and the occurrence of pinholes is reduced due to the high thickness of the protective layer 8, so that a sufficient water vapor permeability coefficient is obtained, but the amount of light transmission decreases, resulting in a decrease in the power generation amount of the solar cell.
[0044] 1 illustrates an example in which the entire laminate 7 is covered with the protective layer 8, but the solar cell module of the embodiment is not limited to this. In the solar cell module of the embodiment, it is sufficient that the protective layer covers at least the end face of the second photoactive layer.
[0045] The sealing material 9 is not particularly limited, but examples thereof include ethylene vinyl acetate copolymer (EVA), polyolefin elastomer (POE), olefin-based thermoplastic elastomer (TPO), polyethylene, ionomer, silicone, and the like.
[0046] The water vapor permeability coefficient of the sealing material 9 is 10g·mm / m 2 / day or less is preferable, and 1g·mm / m 2 / day or less is more preferable, and 0.9g·mm / m 2 / day or less. When the water vapor transmission coefficient of the encapsulant 9 is equal to or less than the upper limit, an inexpensive material can be used for the encapsulant 9. Since the encapsulant 9 is a material used for the entire module, the module can be manufactured inexpensively.
[0047] The water vapor permeability coefficient of the sealing material 9 can be measured by a method similar to that for measuring the water vapor permeability coefficient of the material of the protective layer 8 .
[0048] The thickness of the sealing material 9 is preferably 20 μm or more and 1000 μm or less, more preferably 200 μm or more and 500 μm or less, and even more preferably 300 μm or more and 500 μm or less. If the thickness of the sealing material 9 is equal to or more than the lower limit, the mass increases and the module becomes rigid. If the thickness of the sealing material 9 is equal to or less than the upper limit, the mass decreases and the flexibility of the module improves.
[0049] The first buffer layer 16 is a layer that transports and preferentially extracts electrons or holes, and functions as a hole transport layer or an electron transport layer.
[0050] The second buffer layer 17 is a layer that transports and preferentially extracts electrons or holes, and functions as a hole transport layer or an electron transport layer.
[0051] When the second buffer layer 17 functions as a hole transport layer or an electron transport layer, it is preferable that the second buffer layer 17 is made of an inorganic oxide. When the second buffer layer 17 functions as a hole transport layer, it is preferable that the second buffer layer 17 is made of titanium oxide. When the second buffer layer 17 functions as an electron transport layer, it is preferable that the second buffer layer 17 is made of tin oxide.
[0052] When the second buffer layer 17 is used as a hole injection layer, its thickness is preferably 30 nm or less, and may be 15 to 25 nm. This is because the film resistance as a hole injection layer can be reduced and the conversion efficiency can be increased. On the other hand, the thickness as a hole injection layer can be 5 nm or more.
[0053] When the second buffer layer 17 is used as an electron transport layer, its thickness is preferably 30 nm or less, and may be 15 to 25 nm. This is because the film resistance as an electron transport layer can be reduced and the conversion efficiency can be increased. On the other hand, the thickness as an electron transport layer can be 5 nm or more.
[0054] The antireflection layer 18 is composed of one or more of halogen compounds such as lithium fluoride and magnesium fluoride, silicon nitride, etc. By providing the antireflection layer 18, it is possible to suppress the reflection of sunlight on the light-receiving surface side of the solar cell module 1.
[0055] The first substrate 12 and the second substrate 13 sandwich the laminate 7 covered with the protective layer 8 and the sealing material 9 to protect the laminate 7. The first substrate 12 may be a glass substrate or a back sheet for a solar cell. The second substrate 13 may be a glass substrate.
[0056] The first extracting electrode 14 and the second extracting electrode 15 are made of one or more conductive materials such as aluminum, silver, copper, carbon, and the like.
[0057] In the solar cell module 1 shown in FIG. 1, the end surface 5a of the second photoactive layer 5 is covered with a protective layer 8 having a water vapor permeability coefficient smaller than that of a general sealing material. This makes it possible to protect the second photoactive layer 5 from outside air and moisture. In addition, since the protective layer 8 is formed inside the sealing material 9 and the water vapor permeability coefficient of the protective layer 8 is smaller than that of the sealing material 9, the second photoactive layer 5 is not exposed to moisture generated from the sealing material 9 during sealing. Therefore, the second photoactive layer 5 is not damaged by moisture.
[0058] Second embodiment Fig. 2 shows a solar cell module 100 according to a second embodiment. In Fig. 2, the same components as those in the solar cell module 1 shown in Fig. 1 are denoted by the same reference numerals and will not be described. The solar cell module 100 shown in Fig. 2 is provided with a second protective layer 101 that covers the protective layer (first protective layer) 8 in addition to the solar cell module 1 shown in Fig. 1.
[0059] The material of the second protective layer 101 may be the same as that of the first protective layer 8. The material of the first protective layer 8 and the material of the second protective layer 101 may be the same or different. When the material of the first protective layer 8 and the material of the second protective layer 101 are different, it is preferable that the water vapor permeability coefficient of the material of the first protective layer 8 is small and that of the material of the second protective layer 101 is small. For example, it is preferable that the material of the first protective layer 8 is a paraxylylene-based polymer and the material of the second protective layer 101 is an amorphous fluoropolymer. In this case, the first protective layer 8 suppresses the permeation of water vapor, and the second protective layer 101 physically protects the second photoactive layer 5 and the laminate 7. That is, the pinholes generated in the first protective layer 8 are covered by the second protective layer 101, and the gas barrier property can be improved by structurally devising.
[0060] The thickness of the second protective layer 101 is preferably 0.01 μm or more and 10 μm or less, more preferably 0.05 μm or more and 4 μm or less, and even more preferably 0.4 μm or more and 0.9 μm or less. If the thickness of the second protective layer 101 is less than the lower limit, not only the amount of gas permeation increases due to the reduction in the thickness of the protective layer 8, but also the occurrence of pinholes becomes significant, and a sufficient water vapor permeability coefficient cannot be obtained. Furthermore, the effect of preventing the intrusion of low molecular components such as moisture generated during vacuum lamination and subsequent power generation is reduced. In addition, the effect of preventing the outflow of components constituting perovskite during vacuum lamination and subsequent power generation is reduced. As a result, the solar cell characteristics are reduced immediately after sealing, and the power generation time is shortened. If the thickness of the second protective layer 101 is less than the upper limit, the amount of gas permeation decreases and the occurrence of pinholes is reduced due to the high thickness of the protective layer 8, so that a sufficient water vapor permeability coefficient can be obtained, but the amount of light transmission decreases, resulting in a decrease in the power generation amount of the solar cell.
[0061] The solar cell module 100 shown in Fig. 2 may have three or more protective layers. When three or more protective layers are provided, all of the protective layers may be made of the same material or different materials.
[0062] In the solar cell module 100 shown in FIG. 2, by providing the first protective layer 8 and the second protective layer 101, pinholes in the first protective layer 8 can be covered, and durability can be further improved.
[0063] The solar cell module of the embodiment can also be applied to a solar cell module having only one photoactive layer.
[0064] [Solar cell module manufacturing method] A method for manufacturing a solar cell module of an embodiment includes a protective layer forming step of forming a protective layer on at least an end face of the second photoactive layer, and a sealing step of sealing the laminate with a sealing material via the protective layer by vacuum lamination.
[0065] A method for manufacturing a solar cell module according to an embodiment will be described with reference to FIG. In the protective layer forming step, a material for the protective layer 8 is applied to the end surface 7a of the laminate 7, and the material is cured to form the protective layer 8.
[0066] The amount of material for the protective layer 8 to be applied is not particularly limited, but is set so that the thickness of the protective layer 8 falls within a predetermined range.
[0067] The material of the protective layer 8 can be applied by, for example, a method of synthesizing the material from a pyrolysis gas of the raw material, dipping, spin coating, or die coating.
[0068] In the sealing step, the laminate 7 is sealed with a sealant 9 via the protective layer 8 by vacuum lamination.
[0069] In the manufacturing method of the solar cell module of the embodiment, it is preferable to perform the protective layer forming step before the sealing step. In a state where the second photoactive layer 5 and the laminate 7 are covered with a protective layer 8 having a small water vapor permeability coefficient, the laminate 7 is sealed with a sealing material 9 through the protective layer 8 by vacuum lamination, thereby reducing damage to the second photoactive layer 5 caused by moisture generated from the sealing material 9 in the sealing step. In addition, in a state where the second photoactive layer 5 and the laminate 7 are covered with the protective layer 8, the second photoactive layer 5 is prevented from being directly exposed to a reduced pressure state in the sealing step, and damage to the second photoactive layer 5 caused in a vacuum and overheated state can be reduced. Usually, vacuum lamination is performed at a low temperature and in a short time, but in the manufacturing method of the solar cell module of the embodiment, the second photoactive layer 5 and the laminate 7 are covered with a protective layer 8 having a small water vapor permeability coefficient, and the sealing step is performed in a state where damage caused by moisture is reduced, so that the same lamination conditions as those of conventional silicon solar cells can be used. Furthermore, there are no restrictions on the lamination process of the encapsulant, and the inherent performance of the encapsulant can be exhibited without insufficient crosslinking rate or gelation rate.
[0070] Although some embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and spirit of the invention. [Explanation of symbols]
[0071] Reference Signs List: 1...solar cell module, 2...first electrode, 3...first photoactive layer, 4...intermediate conductive layer, 5...second photoactive layer, 6...second electrode, 7...laminated body, 8...protective layer, 9...sealant, 10...transparent electrode layer, 11...metal electrode layer, 12...first substrate, 13...second substrate, 14...first extraction electrode, 15...second extraction electrode, 16...first buffer layer, 17...second buffer layer, 18...anti-reflection layer.
Claims
1. a laminate including a first electrode, a first photoactive layer, an intermediate conductive layer, a second photoactive layer made of a photoactive material having a perovskite crystal structure, and a second electrode; a protective layer covering at least an end face of the second photoactive layer; a sealant that seals the laminate via the protective layer, the water vapor transmission coefficient of the protective layer is smaller than the water vapor transmission coefficient of the sealing material and is 0.1 g·mm / m 2 / day or less; A solar cell module, wherein the material of the protective layer is a paraxylylene-based polymer or an amorphous fluoropolymer.
2. The solar cell module of claim 1 , wherein at least one of a buffer layer and an anti-reflection layer is provided between the second photoactive layer and the protective layer.
3. 2. The solar cell module according to claim 1, comprising two or more protective layers, at least one of the protective layers being made of a paraxylylene-based polymer, and at least one of the protective layers being outside the paraxylylene-based polymer protective layer being made of an amorphous fluoropolymer.
4. A method for manufacturing a solar cell module comprising: a stacked body in which a first electrode, a first photoactive layer, an intermediate conductive layer, a second photoactive layer made of a photoactive material having a perovskite crystal structure, and a second electrode are stacked; a protective layer that covers at least an end face of the second photoactive layer; and a sealing material that seals the stacked body via the protective layer, a protective layer forming step of forming a protective layer on at least an end surface of the second photoactive layer; and a sealing step of sealing the laminate with a sealant via the protective layer by vacuum lamination, The water vapor transmission coefficient of the protective layer is smaller than the water vapor transmission coefficient of the sealing material and is 0.1 g mm / m 2 / day or less, A method for manufacturing a solar cell module, wherein the material of the protective layer is a paraxylylene-based polymer or an amorphous fluoropolymer.
5. The method for manufacturing a solar cell module according to claim 4 , wherein the protective layer forming step is performed before the sealing step.
Citation Information
Patent Citations
Double-glass solar module
CN208985997U
Photoelectric conversion device and photovoltaic power generator
JP2006100069A
Solar cell module and manufacturing method of the same
JP2012089663A
Solar cell and its manufacturing method
JP2023508244A
Solar assembly with a multi-ply barrier layer and individually encapsulated solar cells or solar cell strings
US20070295387A1